STUDI KOMPARASI TENTANG KELEBIHAN DAN KEKURANGAN HARTA WARISAN DALAM KITAB UNDANG-UNDANG HUKUM PERDATA DAN KOMPILASI HUKUM ISLAM - BAIQ ROHATUL ASNA JALILAH; Fatahullah Fatahullah (Private Law, 2023)
The purpose of this study is to analyze the regulation of the surplus and shortage of inheritance based on the Indonesian Civil Code and Compilation of Islamic Law and the type of settlement of the surplus and shortage of inheritance. The results of this study indicate that in the regulation, the surplus and shortage of inheritance based on the Indonesia Civil Code is included in incorting and inbreng material. Whereas in the Compilation of Islamic Law, the regulation of the surplus and shortage of inheritance is called 'aul and radd. The type of settlement of the surplus and shortage of inherited assets in each concept has its way of settlement in each regulation. Settlement of surplus and shortage of inherited assets that are carried out in incorting and inbreng is by returning or reducing inherited assets when a right of an heir has been violated. The purpose of holding incorting and inbreng is to slightly equalize the distribution of inheritance among heirs. In the Compilation of Islamic Law itself, the type of settlement of the surplus and shortage of inherited assets is carried out by dividing all inherited assets among fellow heirs.